Analisis Faktor Yang Mempengaruhi Efektivitas Pengelolaan Keuangan Daerah Pada Pemerintah Daerah Kabupaten Teluk Bintuni - Patiran, Faustina C. C; Siahay, Adolf Z. D; Allolayuk, Paulus K. (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2024)
This study aims to analyze the factors that affect the effectiveness of regional financial management. Factors affecting the effectiveness of regional financial management are measured by variables of human resource quality, functional supervision, regional financial information system and internal control system. The research approach used is associative. The sampling technique used in this study is purposive sampling with a total of 115 respondents at the OPD and the Teluk Bintuni Regency Inspectorate. Data collection was carried out by distributing questionnaires. Data analysis uses multiple linear regression with the help of SPSS. This study show results that human resources, functional supervision, regional financial accounting system, and internal control system affect the effectiveness of regional financial management in the Teluk Bintuni Regency Regional Government.